2016
DOI: 10.1155/2016/6081905
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Long Term Supervised and Assisted Physiotherapy in Postsurgery Oral Submucous Fibrosis Patients

Abstract: Oral submucous fibrosis is one of the leading potentially malignant disorders prevailing in India. A number of conservative and surgical treatment options have been suggested for this potentially malignant disorder (Arakeri and Brennan, 2013). While the role of physiotherapy has been highlighted in the conservative management, its importance in postsurgical cases to avoid scar contracture and subsequent relapse has not been given due importance in the literature. The following is a case report of a male patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In a study done by Kale et al, they found that adequate mouth opening of 43 mm at 6 months was achieved by surgical intervention followed by vigorous mouth opening physiotherapy exercise in the single patient that was included in their case report. 14…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Kale et al, they found that adequate mouth opening of 43 mm at 6 months was achieved by surgical intervention followed by vigorous mouth opening physiotherapy exercise in the single patient that was included in their case report. 14…”
Section: Discussionmentioning
confidence: 99%
“…Aversion of the patient towards physiotherapy is primarily attributed either to negligence and underestimation of its importance or post-operative pain. 4 The indispensable role of physiotherapy might also be obstructed if there is a co-existence of another debilitating condition incapacitating the patient. Such a possibility can be explored with respect to the presence of an elongated styloid process (ESP) which could contribute adversely to the failure of the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…It is a precancerous, debilitating condition, forming a major portion of the disease spectrum encountered when the patients present to both general dentists and oral and maxillofacial surgeons alike. It is progressive and insidious in nature, causing epithelial atrophy which hastens malignant transformation in about 7-30 % and dysplasia in 25 % of cases [3,4]. Disturbingly, this malady has gained attention of the youth and children, especially males, due to the popularity of commercially prepared arecanut and tobacco preparations with 20 million Indian farmers engaged in tobacco production.…”
mentioning
confidence: 99%